Longitudinal Trends in Quality of Life and Physical Function in Frail Older Dialysis Patients: A Comparison of Assisted Peritoneal Dialysis and In-Center Hemodialysis. Issue 2 (March 2019) - Iyasere, Osasuyi; Brown, Edwina; Gordon, Fabiana; Collinson, Helen; Fielding, Richard; Fluck, Richard; Johansson, Lina; Morgan, Neal; Stoves, John; Vardhan, Anand; Woodrow, Graham; Davenport, Andrew
Background: In-center hemodialysis (HD) has been the standard treatment for older dialysis patients, but reports suggest an associated decline in physical and cognitive function. Cross-sectional data suggest that assisted peritoneal dialysis (aPD), an alternative treatment, is associated with quality of life (QoL) outcomes that are comparable to in-center HD. We compared longitudinal changes in QoL between modalities. Methods: We enrolled 106 aPD patients, matched with 100 HD patients from 20 renal centers in England and Northern Ireland. Patients were assessed quarterly for 2 years using the Hospital Anxiety and Depression Scale (HADS), SF-12 physical and mental scores, symptom score, Illness Intrusiveness Rating Scale (IIRS), Barthel's score, and the Renal Treatment Satisfaction Questionnaire (RTSQ). Mixed model analysis was used to assess the impact of dialysis modality on these outcomes during follow-up. P values were adjusted for multiple significance testing. Results: Multivariate analysis showed no difference in any of the outcome measures between aPD and HD. Longitudinal trends in outcomes were also not significantly different. Higher age at baseline was associated with lower IIRS and RTSQ scores during follow-up. One-hundred and twenty-five (60.6%) patients dropped out of the study: 59 (28.6%) died, 61 (29.6%) withdrew during follow-up, and 5 (2.5%) were transplanted. Conclusions: Quality of life outcomes in frail older aPD patients were equivalent to those receiving in-center HD. Assisted PD is thus a valid alternative to HD for older people with end-stage kidney disease (ESKD) wishing to dialyze at home.